2004
DOI: 10.1289/ehp.6677
|View full text |Cite
|
Sign up to set email alerts
|

Clofibrate-induced gene expression changes in rat liver: a cross-laboratory analysis using membrane cDNA arrays.

Abstract: Microarrays have the potential to significantly impact our ability to identify toxic hazards by the identification of mechanistically relevant markers of toxicity. To be useful for risk assessment, however, microarray data must be challenged to determine reliability and interlaboratory reproducibility. As part of a series of studies conducted by the International Life Sciences Institute Health and Environmental Science Institute Technical Committee on the Application of Genomics to Mechanism-Based Risk Assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 51 publications
3
27
1
Order By: Relevance
“…In contrast to a report in rat liver (Baker et al, 2004), no increases of Cyp4a1 or epoxide hydrase, a decrease of PPAR, or alterations of proliferation-associated genes were observed. Similarly, effects of CF on proliferationassociated genes in rat hepatocytes were not observed.…”
Section: Clofibrate (Cf)contrasting
confidence: 99%
“…In contrast to a report in rat liver (Baker et al, 2004), no increases of Cyp4a1 or epoxide hydrase, a decrease of PPAR, or alterations of proliferation-associated genes were observed. Similarly, effects of CF on proliferationassociated genes in rat hepatocytes were not observed.…”
Section: Clofibrate (Cf)contrasting
confidence: 99%
“…While several recent studies have addressed interlaboratory variation in microarray results, comparisons were between pooled samples (Baker et al, 2004;Chu et al, 2004;Ulrich et al, 2004;Waring et al, 2004). Thus, individual variation was not addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The observed discrepancies in expression profiles for individual genes might be due to chemical (for example, impure substance), animal, microarray, test reagent, procedure of animal testing and gene expression analysis. Baker et al (2004) have reported a cross-laboratory analysis using membrane cDNA arrays (Baker et al, 2004) and obtained essentially the same findings. Three separate animal tests were conducted and three separate gene expression analyses carried out under different conditions in their study, while three separate animal tests were conducted according to the same protocol and gene expression analysis carried out at one laboratory in our study.…”
Section: Resultsmentioning
confidence: 61%
“…They confirmed reasonable agreement in gene expression results between laboratories and across platforms, and the observed discrepancies in expression profiles for individual genes were largely due to platform differences and approaches to data analysis rather than to biological or interlaboratory variability. Baker et al also reported a cross-laboratory analysis of the same compounds using membrane cDNA arrays, including comparison of the gene expression profiles generated from pooled and individual RNA samples (Baker et al, 2004). They found results from all three laboratories to demonstrate a considerable degree of similarity.…”
Section: Introductionmentioning
confidence: 99%